An Evaluation of Surface Urban Heat Islands in Two Contrasting Cities - Hamoodi, Mustafa Naem (Curtin University, 2018)
This thesis presents a comparative study on surface urban heat islands effects in Baghdad and Perth. The first part evaluates expansion of built-up areas and quantifies its effects on land surface temperature patterns. The second part examines the extent to which the urban thermal environment is influenced by spatial patterns of land use and land cover (LULC) categories. The final part investigates the thermophysical behaviour of various urban LULC categories using albedo and LST parameters.